Penggunaan Aplikasi Peduli Lindungi Sebagai Alternatif Pengurangan Penyebaran Covid-19 di Kota Surabaya - Fitriyanti, Victoria; Devita, Hariani (Institut Riset dan Pengembangan Indonesia, 2022)
The corona virus (Covid-19) that is currently sweeping the world has had a huge impact on social and economic life, even the main thing that has an impact on the world of health. Covid-19 has been declared by WHO as a pandemic. The spread of the virus is very fast in almost all countries in the world, it has made big changes in human life. State governments, especially Indonesia, have made various policies to prevent the spread of this massive virus. Health Communication is carried out by the government throughmedia sharing in conveying messages related to Covid-19 to the public. One of the media used is a Covid-19 tracking application called PeduliLindungi. This communication technology is expected to provide education and reduce the spread of the virus. This study aims to examine the role and benefits of development communication through the PeduliLindungi application as a media for health communication between the Indonesian government and the people of Surabaya. This study uses both health and media communication approaches to age theory. As well as. Activation of the application is a social movement in building awareness and advocating for the use of the internet as a source of news as information control. The COVID-19 pandemic has had a major impact on many aspects of consumers' lives, including how to access health services. One alternative approach that has emerged is Mobile Health as an alternative access mechanism for health services in the midst of a pandemic and health care.